Rehabilitation of Women Who Have Undergone Tubectomy (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Purpose: Surgical treatment of ectopic pregnancy often involves removing the tube in which the pathological pregnancy has developed (salpingectomy), but sometimes it can be preserved (salpinotomy). Laparoscopy can be performed when planning a pregnancy after an ectopic with one tube or with two tubes, one of which has undergone surgical intervention. It is usually performed for diagnostic and therapeutic purposes, as this operation allows you to visually assess the condition of the pelvic organs and, if necessary, surgically correct any pathologies identified.Materials and methods: The abdominal cavity was drained of exudate and the abdominal cavity was cleaned, which was considered appropriate, since inflammatory exudate removes cellular elements that contribute to the development of adhesions. In addition, this led to a rapid normalization of temperature after surgery. During dynamic laparoscopy, chromohydrotubation was performed to determine the patency of the fallopian tubes, which was not only diagnostic, but also therapeutic in nature, since it exerted a hydraulic effect on the adhesions formed in the ampullary parts of the tubes and mechanically removed the accumulated fibrin in the lumen of the fallopian tubes.Results of the study. Adhesions were detected in 45 patients (64.2%) during dynamic laparoscopy, of which: in 15 patients - after laparoscopic access and in 30 patients - after laparotomy. In all patients who underwent dynamic laparoscopy, adhesions were in the form of soft, loose, avascular adhesions, which were easily separated with blunt instruments. Repeated dynamic laparoscopy in 15 patients showed no reorganization of adhesions. According to the data of chromohydrotubation performed during dynamic laparoscopy: in 51 patients the tube or tubes were passable (this was 72.9%), in 19 patients they were impassable (27.1%). 3 months after the operation, all patients were re-examined for patency of the fallopian tubes using kymographic pertubation or ultrasound sonocontrast hysterosalpingoscopy. The data from these studies are consistent with those obtained from chromohydrotubation performed during dynamic laparoscopy (tubules were patent in 72.9% of patients), which is significantly higher than in the general population of patients operated on for ectopic pregnancy.Conclusion : The study showed that dynamic laparoscopy in the early postoperative period is an effective method for diagnosing and preventing adhesions in patients undergoing surgery for tubal pregnancy, which helps to optimize the results of surgical treatment of ectopic pregnancy and preserve reproductive function in patients.After an unsuccessful attempt to get pregnant and bear a child, as well as after surgery for ectopic pregnancy, every woman who has experienced this difficult situation asks herself the question: “Is it possible to get pregnant after an ectopic pregnancy? What are the chances that the next time the fetus will develop without complications and the whole process will end with the birth of a healthy child?”. Practice shows that the probability of a successful outcome is quite high. In order for the next pregnancy to occur and proceed normally, it is necessary to responsibly approach the possibility of conception, undergo a comprehensive examination, identify the causes of the development of an ectopic pregnancy, undergo rehabilitation and, if necessary, treat the identified pathologies.